From stridor to symptom relief; management of pediatric Kommerell's diverticulum and vascular rings in Palestine [2016–2024]: a single center cohort study - Amouri, Mohammad; Deeb, Salahaldeen; Sourkhi, Nour; Qasim, Sara; Abu Hadeed, Boshra; Atatra, Khalil Omar; Nasereddin, Ahmad (Frontiers in Pediatrics, 2025)
BackgroundKommerell's diverticulum (KD) with vascular rings is an uncommon cause of pediatric airway and feeding symptoms, and data from the Arab region are scarce. We report a Palestinian cohort of all diagnosed and managed cases, describing presentation, diagnostics, and management.MethodsWe retrospectively studied all children at Al-Makassed Hospital (Jerusalem) from 2016 to 2024 who were diagnosed with vascular rings + KD confirmed by imaging or intra-operative findings. We abstracted demographics, symptoms, test performance, anatomy, treatments, and peri-operative course and follow-up. Primary outcomes were diagnostic yield and improvement at last visit.ResultsFourteen patients were included; median age at diagnosis was 8 months (IQR 2–15), symptom onset 15 days (0–83). Thirteen (92.9%) were symptomatic; stridor (64.3%), recurrent wheeze (35.7%), and dysphagia/choking (28.6%) predominated; 42.9% had prior misdiagnoses. Barium swallow was positive in 7/8 (87.5%), echocardiography in 5/9 (55.6%), bronchoscopy in 10/12 (83%), and CT angiography (CTA) confirmed anatomy in 13/13 (100%). Anatomy included right aortic arch (RAA) with aberrant left subclavian artery in 8/14 (57.1%), double aortic arch in 4/14 (28.6%), and innominate artery compression in 2/14 (14.3%); 57.1% had minor intracardiac anomalies. Thirteen children (92.9%) underwent surgery (ligamentum division, diverticulectomy ± subclavian transfer, aortopexy, or double-arch division); one mild innominate compression case was observed. All were discharged alive; one late death occurred. At last follow-up, 7/13 survivors were asymptomatic and 6/13 had residual but improved symptoms. Median hospital stay was 18 days (IQR 7–25).ConclusionKD-associated rings present early yet are frequently delayed in diagnosis. CTA is definitive, and tailored surgery yields meaningful, often complete, symptom relief with acceptable morbidity.